ETS PSYCHOMETRIC CONTRIBUTIONS: FOCUS ON TEST SCORES. Issue 1 (8th August 2014) - Moses, Tim
ABSTRACT: The purpose of this report is to review ETS psychometric contributions that focus on test scores. Two major sections review contributions based on assessing test scores' measurement characteristics and other contributions about using test scores as predictors in correlational and regression relationships. An additional section reviews additional contributions that integrate test scores' measurement aspects with correlational and regression uses.